Assessment of Infrastructure Development Approach in Newly Created Districts in Zambia: Case Study - Kabwe, Chimanga; Innocent, Musonda; Muleya, Franco (CSID Journal of Infrastructure Development, 2023)
This article evaluates the infrastructure development plans in Zambia's newly established districts, primarily focusing on assessing their effectiveness. Infrastructure development encompasses various strategies, and this study investigates the factors influencing the selection of these strategies for implementing infrastructure projects in Zambia. Through structured interviews and questionnaires distributed to 500 respondents, the research highlights the critical role of community involvement. Communities play a pivotal role in identifying essential amenities, setting priorities for infrastructure construction, incorporating their ideas, and participating in the planning process for executing infrastructure projects. The analysis reveals that community members held varying perspectives on the significance of infrastructure in fostering community integration. However, it also indicates that community involvement in these initiatives was below the desired levels, potentially leading to infrastructure projects that may not entirely align with community preferences. This research underscores the vital importance of infrastructure development, as it establishes the foundation for an improved quality of life encompassing health, education, water supply, sanitation, and transportation.